BLOCKCHAIN-BASED DECENTRALIZED USER AUTHENTICATION SCHEME FOR LETTER OF GUARANTEE IN FINANCIAL CONTRACT MANAGEMENT - A. , Sasikumar; B, Karthikeyan; S., Arunkumar; P., Saravanan; V, Subramaniyaswamy; Ravi, Logesh (Malaysian Journal of Computer Science, 2022)
The use of blockchain technology in the financial contract management system leads many challenges for user authentication and key distribution. In traditional financial system, the core endeavor with strong letter of guarantee play an irreplaceable role in the supply chain management. In this context, fraud in financial contract management is severe problem for economical growth. To overcome the problems of the conventional transaction process, in this paper, we develop a user access control and key management scheme that uses blockchain decentralized network to manage the letter of guarantee. This decentralized network platform can helps the problem of no trust among the users, improves the efficiency of data transmission, reduces costs, and provides better financial services to the relevant parties in the supply chain. The proposed user authentication is developed based on the deterministic encryption algorithm to achieve decentralized security for trusted data transmission. Finally, the experimental results shows that the computation cost of the proposed authentication increases due to the rising of number of customer added to the blockchain network. Overall the proposed authentication scheme most suitable for banking system to issue the LoG contract in right time.